THE EFFECTS OF LASER ENGRAVING METHODS ON CERAMIC SURFACES - Betül AYTEPE SERİNSU (Fırat University, 2019)
Laser is being commonly used in health, graphic, advertising sectors and several other fields of industry nowadays. It is also eligible for experimental practices in arts. That, laser is applied in very sensitive operations like eye surgeries, brings it to mind that it can also be used while making very fragile art works. With the laser engraving method, successful effects are being obtained through several recent practices. In previous researches, the laser engraving method has been applied on ceramic bodies and as a result, successful effects have been obtained as ceramic is a material which is, suitable to engrave. In this research, digitally designed patterns have been engraved on bisque fired ceramic bodies by applying glaze, pigment colours, oxides, engobes and the results have been discussed following the glaze firing. The resulting effects show that, sinterization occurred on the surfaces that were exposed to high temperatures through laser beam and to a large extent the patterns have been successfully copied on the surfaces. This research contains the application of a digitally designed pattern on a glazed or unglazed ceramic surface and an experimental application process.